2019
DOI: 10.2147/opth.s185304
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety of posterior chamber implantable phakic contact lens for the correction of myopia

Abstract: PurposeTo review the safety of the implantable phakic contact lens (IPCL V1, Caregroup Sight Solutions, India) for correction of myopia and myopic astigmatism.MethodsRetrospective interventional case series including 134 eyes which underwent IPCL implantation for correction of myopia and myopic astigmatism at a tertiary eye care hospital in South India. Intraoperative and postoperative complications were analyzed. The following parameters were analyzed at preoperative and 1, 6 and 12 month postoperative visits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 19 publications
5
30
1
5
Order By: Relevance
“…And a similar result was obtained in a previous study, but only with a 6 month follow-up for the IPCL V 2.0 model [24]. However, with the previous IPCL platform (V 1.0) evaluated by other authors, using a surgical technique with the aid of viscoelastic substances, similar safe values were obtained [22,23].…”
Section: Safety Concerns: Intra-ocular Pressure Cornea (Endothelial supporting
confidence: 88%
See 3 more Smart Citations
“…And a similar result was obtained in a previous study, but only with a 6 month follow-up for the IPCL V 2.0 model [24]. However, with the previous IPCL platform (V 1.0) evaluated by other authors, using a surgical technique with the aid of viscoelastic substances, similar safe values were obtained [22,23].…”
Section: Safety Concerns: Intra-ocular Pressure Cornea (Endothelial supporting
confidence: 88%
“…Only 1.9% of eyes got 20/32 10 UDVA. Good refractive outcome was similar to what was previously reported for IPCL [22][23][24], which gives information about the efficiency of this lens to correct ametropias. Moreover, the obtained defocus curve gives information about how patients were capable of seeing at different distances without the aid of spectacles.…”
Section: Visual Performancesupporting
confidence: 87%
See 2 more Smart Citations
“…The authors concluded IPCL to be a safe and effective treatment modality. 20 We did not find any indication that safety will become a major problem after implantation of the presbyopic IPCL. In one case in our group of patients, an explantation and re-implantation during the primary surgical procedure was necessary because the IOL turned out to be implanted upside-down due to the shooting process.…”
Section: Discussionmentioning
confidence: 62%